On Conjugacy of Cartan Subalgebras in Non-FGC Lie tori - Chernousov, V. (2016)
We establish the conjugacy of Cartan subalgebras for generic Lie tori “of type A”. This is the only conjugacy problem of Lie tori related to Extended Affine Lie Algebras that remained open.